STUDI FENOMENOLOGI TENTANG KOMUNIKASI REMAJA PENGGUNA NARKOBA - Evline Yulianty (Indonesian Journal of Dialectics, 2012)
This study aims to determine the communication process is carried out by young drug users with fellow users, counselors, in the group and with this parents. This research located in RSKO Jakarta. This study uses perspective of phenomenological and the theory of Symbolic Interaction, as a benchmark to explore perceptions and information and communication behavior of the informants saw as a research subject. Encode obtained by in-depth interviews, observations to participate, and study documentation. Research methods with qualitative approaches.  The result showed that: first, the process of communication with fellow users. The process of communication with other users occurs in formal and informal situations. In a formal situation generally occurs in learning activities. While the informal situations, such as ini everyday conversation, residents are free to express what’s on their minds. For example, residents share their stories of life experience while still using the drug to experience during in RSKO Jakarta. Second, the communication process is intended to bring up the character and mental strength in the residen so really can not leave or forget the drugs. Third, the communication process within the group. The communication process is intentionally held for residents accustomed to solve a problem together. In addition, in any activity of discussion, resident will feel challenged to be motivated to solve probelms together with other colleagues and their vision. In addition, as for the purpose of the communication process ini this group, in orther to build confidence in dealing with residens outside world or society. Fourth, the process of communication with parents. In this communication process, the role of parents is very great in favor of the resident’s mental develompment and character. In other words, adolescent drug users need attention from parents or family. Therefore, necessary role in supporting the healing of the resident family, namely: the visit, support and motivation, trust, and praise.